2017
DOI: 10.1021/acs.jpca.6b10314
|View full text |Cite
|
Sign up to set email alerts
|

Use of Spectroscopic Techniques for Evaluating the Coupling of Porphyrins on Biocompatible Nanoparticles. A Potential System for Photodynamics, Theranostics, and Nanodrug Delivery Applications

Abstract: Modern medicine has been searching for new and more efficient strategies for diagnostics and therapeutics applications. Considering this, porphyrin molecules have received great interest for applications in photodiagnostics and phototherapies, even as magnetic nanoparticles for drug-delivery systems and magnetic-hyperthermia therapy. Aiming to obtain a multifunctional system, which combines diagnostics with therapeutic functions on the same platform, the present study employed UV/vis absorption and fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 77 publications
2
13
0
2
Order By: Relevance
“…The binding constant was similar to that for the binding of nonfunctional porphyrin to the gold nanosurface, as investigated by Shaikh et al, and for the interaction of TPPS to magnetic iron oxide nanoparticles and other nanosystems. 27 , 37 , 42 44 It is likely that porphyrin got adsorbed on the AuNP surfaces through the coordination interaction between gold and pyrrolic nitrogen atoms of the porphyrin ring and formed a strong association complex.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The binding constant was similar to that for the binding of nonfunctional porphyrin to the gold nanosurface, as investigated by Shaikh et al, and for the interaction of TPPS to magnetic iron oxide nanoparticles and other nanosystems. 27 , 37 , 42 44 It is likely that porphyrin got adsorbed on the AuNP surfaces through the coordination interaction between gold and pyrrolic nitrogen atoms of the porphyrin ring and formed a strong association complex.…”
Section: Resultsmentioning
confidence: 99%
“…However, pyrrolic nitrogen atoms have strong propensities to be involved in coordination with the metal surface. 27 It could be a strong association complex. ITC measurements established the binding/association constant for binding of TPPS to gold nanoparticles to be about 3 × 10 5 M –1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, in comparison with free hemin, both kinds of nanoparticles exhibited a high, strong near-infrared absorption, which is highly appropriate for absorption-based applications, such as photothermal therapy and photoacoustic imaging [18]. Magno et al [19] also reported that porphyrin nanoparticles with near-infrared absorption have received considerable interest for applications in phototherapies and photodiagnostics, even as magnetic nanoparticles for magnetic-hyperthermia therapy and drug-delivery systems.…”
Section: Resultsmentioning
confidence: 99%
“…The QD surface area A QD ≈ 145 nm 2 is sufficient to adsorb several TPPS 4 molecules ( A TPPS4 ≈ 1.8 nm 2 per unit) [ 40 ], as it was observed for porphyrins interacting with magnetic and gold nanoparticles [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%